HMGB1 Modulates High Glucose-Induced Erroneous Differentiation of Tendon Stem/Progenitor Cells through RAGE/β-Catenin Pathway - Panpan Lu; Guangchun Dai; Liu Shi; Yingjuan Li; Ming Zhang; Hao Wang; Yunfeng Rui (Hindawi Limited, 2024)
The association of tendinopathy with diabetes has been well recognized. Tendon stem/progenitor cells (TSPCs) play critical roles in tendon repair, regeneration, and homeostasis maintenance. Diabetic TSPCs exhibit enhanced erroneous differentiation and are involved in the pathogenesis of diabetic tendinopathy, whereas the underlying mechanism of the erroneous differentiation of TSPCs remains unclear. Here, we showed that high glucose treatment promoted the erroneous differentiation of TSPCs with increased osteogenic differentiation capacity and decreased tenogenic differentiation ability, and stimulated the expression and further secretion of HMGB1 in TSPCs and. Functionally, exogenous HMGB1 significantly enhanced the erroneous differentiation of TSPCs, while HMGB1 knockdown mitigated high glucose-promoted erroneous differentiation of TSPCs. Mechanistically, the RAGE/β-catenin signaling was activated in TSPCs under high glucose, and HMGB1 knockdown inhibited the activity of RAGE/β-catenin signaling. Inhibition of RAGE/β-catenin signaling could ameliorate high glucose-induced erroneous differentiation of TSPCs. These results indicated that HMGB1 regulated high glucose-induced erroneous differentiation of TSPCs through the RAGE/β-catenin signaling pathway. Collectively, our findings suggest a novel essential mechanism of the erroneous differentiation of TSPCs, which might contribute to the pathogenesis of diabetic tendinopathy and provide a promising therapeutic target and approach for diabetic tendinopathy.